Assessment of Micronutrients and Toxic Elements in Rice Grains: Implications for Food Safety and Nutrition - Pokhrel, Galaxy; Silwal, Sachin; Thapa, Sabi; Giri, Swikar; Mahato, Ajaya; Adhikari, Bishisha; Bagale, Shiva; Bhattarai, Bodhbabu; Pokhrel, Ganga Raj (BMC Journal of Scientific Research, 2024)
The complete assessment of micronutrient and toxic elements (Cu, Mo, Sn, Cr, Ni, Zn and Pb) in rice grains and implications for food safety and nutrition is still not understood clearly. Pot experiments were designed to grow the two rice cultivars namely MH63 and LYMZ. For the accurate determination of the micronutrient elements and toxic element, here we used microwave assisted digestion for sample preparation and Inductively Coupled Plasma Mass Spectrometry (ICP-MS) for the determination. Good linearity was maintained over the range studied with correlation coefficients (R2) of 0.999-1.0. This work focused on evaluating these elements in two rice cultivars MH63 and LYMZ. The micronutrient elements and toxic element in the bran and kernel of both the cultivars were detected below the permitted level set by Food and Agriculture Organization of the United States/ World Health Organization(FAO/ WHO). Large portion of the micronutrient elements and toxic elements remain in the bran, very small amounts in the ppb levels remain in the kernel. The translocation of zinc into bran is highest among other nutrient elements. The load of nutrient element copper in the bran of both cultivars remains similar, i.e., 0.006g/kg whereas the toxic element lead in the bran of both cultivar lies below 0.008g/kg. The nutrient element zinc in the kernel of Lymz remains 0.066g/kg where as in MH63 is 0.025g/kg. Nutritionally essential trace element chromium in the kernel of both cultivars lies below 0.004g/kg (1mg/day tolerable limit). The concentration of nutrient elements in two rice cultivars were found to be very close to the minimum levels recommended by Food and agriculture organization (FAO). Thus, the nutrient quality of the rice grain depends on the status of soil, micronutrient element and toxic element concentrations in the permitted range of FAO/ WHO guideline.